Pengaruh Konsentrasi dan Berbagai Jenis Pupuk Organik Cair (POC) Terhadap Hasil Tanaman Kedelai Edamame (Glycine max (L.) Merr.) - Riska Kurniawati; Murti Astiningrum; Wike Oktasari (JURNAL VIGOR, 2022)
This research is to study the effect of concentration and various types of liquid organic fertilizer on yield of Edamame soybeans (Glycine max (L.) Merr.) The research conducted in September 2021 until January 2022 in Sidorejo Village, Bandongan District, Magelang Regency with an altitude of 357 m. The research was conducted with a factorial experiment (4 x 3) arranged in a completely randomized block design with three replications. The first factor is concentration of liquid organic fertilizer 0 ml/l, 10 ml/l, 20 ml/l and 30 ml/l. The second factor is liquid organic fertilizer namely liquid organic fertilizer Nasa, Super Garden and Cow Blood Waste. The results show that the application of liquid organic fertilizer with concentration of 30 ml/l still showed a significant effect on plant height, but the difference in concentration didn’t show a significant effect in the number of filled pods each plants, weight of filled pods each plant, number of fresh seeds each plants, fresh seed weight each plant, fresh soybean seed protein content, and weight 100 dry seeds stored. Liquid organic fertilizer from Cow Blood Waste is able to produce the highest plants height compared to liquid organic fertilizer from Nasa and Super Garden but not significantly different on other parameters. There was no interaction between concentration and type of liquid organik fertilizer for all observed parameters.Keywords: concentration, Edamame soybean, liquid organic fetilizer.